Anisotropy of Random Fields in Stochastic Fem - Knabe, W.; Różyński, G. (Engineering Transactions, 1995)
The anisotropy of a random variable consisting of rectangular local averages of a Gaussian, isotropic and homogeneous random field is presented. The analysis deals with fields having exponential correlation functions. It is shown that such local averages, formed by a mesh of finite elements, generate the anisotropy even if the mesh consists of identical squares.